Kidney and bladder lithiasis in a canine: imaging description - Gallego, Renso (2019)
A case of urolithiasis is reported in a six-year-old Yorkshire male brought to the Veterinary Clinic of the Lasallian University Corporation with a history of bloody urine, difficulties in urinating and, sometimes, small amounts of urine. Complementary tests were performed including simple and contrasted radiography, abdominal ultrasound, urine cytochemistry, urine culture and blood chemistry. The most sensitive diagnostic methods were simple radiography and contrast media that showed four radiopaque structures in the urinary bladder, and abdominal ultrasound where thickened vesical walls and hyperechoic structures with homogeneous edges compatible with uroliths could be observed. Cystotomy was performed for the removal of uroliths.